The FinTech Explorer: A Comprehensive Guide to Case Studies, Course Notes, and Emerging Trends | Explorateur de projets FinTech : Un guide pratique pour études de cas, notes de cours, et nouvelles tendances - Qi, Qianru (Cheryl); Jaffer, Shaista; Ekponon, Adelphe (Université d'Ottawa | University of Ottawa, 2024)
This resource brings together a collection of student-authored case studies that explore how emerging technologies—Artificial Intelligence, Blockchain, Cloud Computing, and Big Data (ABCD)—can revolutionize the financial industry. Cette ressource rassemble une série d’études de cas rédigées par des étudiants qui explorent comment les technologies émergentes - Intelligence Artificielle, Blockchain, le Cloud Computing, et Big Data (ABCD) peuvent révolutionner le secteur financier.
Keywords: financial technology; case study; Open educational resource (OER); Ressource éducative libre (REL)